The COVID-19 Pandemic and Rapid Implementation of Adolescent and Young Adult Telemedicine: Challenges and Opportunities for Innovation - Barney, Angela; Buckelew, Sara; Mesheriakova, Veronika; Raymond-Flesch, Marissa (Journal of adolescent health, 2020)
This study describes the rapid implementation of telemedicine within an adolescent and young adult (AYA) medicine clinic in response to the Coronavirus Disease 2019 (COVID-19) pandemic. While there are no practice guidelines specific to AYA telemedicine, observations made during this implementation can highlight challenges encountered and suggest solutions to some of these challenges. Over the course of several weeks in March, 2020, the Adolescent and Young Adult Medicine Clinic at the University of California San Francisco rapidly replaced most in-person visits with telemedicine visits. This required logistical problem-solving, collaboration of all clinic staff members, and continuous reassessment of clinical practices. This article describes observations made during these processes. Telemedicine visits increased from zero to 97% of patient encounters in one month. The number of visits per month was comparable with that one year prior. While there were limitations to the clinic’s ability to carry out health supervision visits, many general health, mental health, reproductive health, eating disorders, and addiction treatment services were implemented via telemedicine. Providers identified creative solutions for challenges that arose to managing general confidentiality issues as well as specific challenges related to mental health, reproductive health, eating disorders, and addiction care. Opportunities to implement and expand high-quality AYA telemedicine were also identified. The COVID-19 pandemic is leading to widespread telemedicine implementation. While telemedicine seems to be feasible and acceptable for our clinic patients, unanswered questions remain regarding confidentiality, quality of care, and health disparities. Clinical guidelines are also needed to guide best practices for telemedicine in this patient population.